Aspectos Convencionalistas da Filosofia de Willard Quine - Sofia Inês Albornoz Stein (Principia: An International Journal of Epistemology, 2003)
One of the main contributions of philosophers at the end of the 19th century and beginning of the 20th century to philosophy of science and semantics was the thesis inspired in the scientific advances of natural and exact sciences, that there is not a single true theory of what goes on in the empirical world, but rather the possibility of constructing multiple versions, equally satisfactory, of an explanation of the world. In the Vienna Circle, more specifically, the conventionalist movement showed its influence primarily in the writings of Neurath, but also, more subtly, in the texts of Carnap. In this paper, I shall examine the theoretical relations between Quine’s holistic thesis and the conventionalist aspects of his work. In order to do this I will discuss Neurath’s holistic coherentism and of the conventionalist and holistic aspects present in Camap’s work, which merge, mainly in the Aufbau, with reduc-tionist aims. Thus, I intend to help to clarify to what extent Quine’s holism depends on a conventionalist position and to what extent conventionalism, in its turn, can get along with reductionist epistemological remains.